2022
DOI: 10.1002/jso.26883
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on alloplastic breast reconstruction: An analysis of national outcomes

Abstract: Background Immediate alloplastic breast reconstruction shifted to the outpatient setting during the COVID‐19 pandemic to conserve inpatient hospital beds while providing timely oncologic care. We examine the National Surgical Quality Improvement Program (NSQIP) database for trends in and safety of outpatient breast reconstruction during the pandemic. Methods NSQIP data were filtered for immediate alloplastic breast reconstructions between April and December of 2019 (bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Prepandemic studies 13,14 have shown no increase in short-term complications, including readmissions and reoperations, after same-day discharge in patients who underwent mastectomy (with and without implant reconstruction). Two recently published ACS-NSQIP studies 15,16 have also examined the impact of COVID-19 on breast cancer surgery, with findings that corroborate our own. Rubenstein et al 15 found that rates of same-day discharge increased from 2019 to 2020 for patients who underwent mastectomy with alloplastic, but not autologous reconstruction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Prepandemic studies 13,14 have shown no increase in short-term complications, including readmissions and reoperations, after same-day discharge in patients who underwent mastectomy (with and without implant reconstruction). Two recently published ACS-NSQIP studies 15,16 have also examined the impact of COVID-19 on breast cancer surgery, with findings that corroborate our own. Rubenstein et al 15 found that rates of same-day discharge increased from 2019 to 2020 for patients who underwent mastectomy with alloplastic, but not autologous reconstruction.…”
Section: Discussionsupporting
confidence: 85%
“…Rubenstein et al found that rates of same-day discharge increased from 2019 to 2020 for patients who underwent mastectomy with alloplastic, but not autologous reconstruction. Similarly, Chiang et al, who only included patients undergoing alloplastic reconstruction, found an increased rate of outpatient cases in 2020 and did not observe an increased risk of complications compared with inpatient cases. While our study did not stratify patients undergoing mastectomy based on the presence and type of reconstruction, it is likely that very few patients discharged on postoperative day 0 underwent autologous reconstruction, as these patients are typically admitted to hospital for flap monitoring after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a comparison of protocols before, during, and after the COVID‐19 pandemic among 357 patients done by Olimpiadi et al revealed a tripling of outpatient mastectomies and increased use of pectoralis muscle blocks 13 . Among alloplastic reconstruction in particular, COVID‐19 prompted an increase in delayed reconstruction and increased outpatient surgeries 14 …”
Section: Discussionmentioning
confidence: 99%
“…13 Among alloplastic reconstruction in particular, COVID-19 prompted an increase in delayed reconstruction and increased outpatient surgeries. 14 Analysis of complications and outcomes among smaller patient cohorts showed no difference between patients who underwent same-day surgery versus those admitted for observation, [15][16][17][18] which has been supported by aggregate data from larger databases and systematic reviews. [19][20][21][22] The data from our patient cohort further reinforces the safety of same-day discharge after mastectomy and alloplastic reconstruction, whereby no significant increase in complication rate was seen after the institution of an ERAS protocol.…”
Section: F I G U R E 1 Flow Diagram Of Group Divisions Of Included Pa...mentioning
confidence: 91%
“…Studies on implant-and tissue expander-based reconstruction suggests that COVID-19 is not an independent risk factor for postoperative complications, but the same cannot be generalized to autologous reconstruction. 10 Although early work has indicated that the pandemic did not significantly affect 30-day outcomes in autologous flap reconstruction, there was a notable decrease in the proportion of autologous breast reconstruction cases, compared with other types of flaps, and studies with larger patient numbers are needed to make stronger associations. We therefore decided to undertake this study with a large international database to elucidate whether a prior history of COVID-19 affects outcomes in autologous breast reconstruction.…”
mentioning
confidence: 99%